Football Worlds: business and networks during COVID-19. (17th February 2021) - Parnell, Daniel; Bond, Alexander John; Widdop, Paul; Cockayne, David
ABSTRACT: The structure of football can also be conceived as a form of ecosystem, or even a social world, constructed through a network of individuals, within a division of labour, that interact under a set of specific conventions. In this commentary we describe that socially constructed world – Football World. The nature of this structural world makes network theory an appealing framework to explore processes of the football ecosystem during COVID-19. While we focus on the English Premier League, notably this league is embedded within a European and international marketplace it offers relevance for the broader global football ecosystem. We proceed to explore this dynamic Football World by considering how the different collective forms – specifically fans, players and clubs – have been affected by COVID-19. We comment on the potential implications for the connective fabric of the broader network and what these observations mean for potential future research.